Aplikasi Pengenalan Budaya Cirebon untuk Meningkatkan Pemahaman dan Apresiasi terhadap Kearifan Lokal - Sabda Insan Pamungkas; Haris Burhanudin; Hilpad Hidayat; Naufal Ibrahim (Ikatan Ahli Informatika Indonesia, 2025)
This study presents the design and implementation of a mobile-based educational and cultural forum application introducing Cirebon's local culture, developed using the React Native framework and the Design Thinking approach. The application aims to enhance public understanding and appreciation of local wisdom through interactive and accessible digital media. The development process involved stages of empathizing with users, defining needs, ideating, prototyping, and testing. Based on usability testing using the All-Positive System Usability Scale (SUS), the “Cirebon Culture Introduction” application achieved excellent user satisfaction, with most respondents giving a score of 4 (agree) across all indicators and an average satisfaction level above 80%. These results indicate high usability, an engaging interface, and strong cultural relevance. Overall, the iterative Design Thinking process proved effective in producing a user-centered and culturally meaningful application that supports the preservation and promotion of regional culture.